A Spontaneous Thoracic Spinal Epidural Hematoma Causing Hemiplegia and Back Pain - Bedia Gülen; Tolga Turan Dündar; Ertan Sönmez; Güleser Akpınar (Eurasian Journal of Emergency Medicine, 2016)

(untitled)
Spontaneous spinal epidural hematoma (SEH) is an uncommon and emergency condition leading to spinal cord compression. Early diagnosis can be achieved by magnetic resonance imaging (MRI) or computed tomography, but preferably MRI. Surgical decompression is urgent and can relieve neurologic deficits. A 27-year-old man presented to the emergency department with back pain, which began approximately 10 days before. While waiting for the results of biological markers for differential diagnosis, right hemiplegia became evident. Epidural hematoma was revealed with thoracic and lumbar MRI at level T1-T2. Hematoma evacuation and decompression laminectomy was immediately performed.